THE IMPACT OF DISRUPTIVE TECHNOLOGY ON THE PERFORMANCE OF ELECTRICITY COMPANIES IN INDONESIA, STRATEGIC MANAGEMENTPERSPECTIVE - Rio Afrianda (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The power utility industry is in the midst of transition driven by three global movements; de-carbonisation, de-centralisation and digitalisation. The 4.0 revolution direct the electricity environment is becoming more complex than ever before, with rapidly evolving disruptive technologies. This study is to assess empirically how such disruptive technology affect power utility industry. The three most disruptive technologies have been investigated; solar PV, battery energy storage and smart grid. Based on 336 engineers’ reviews from 118 business unit of Indonesia Electricity State Company, it is found that not all disruptive technology does negatively affect the firm performance. The customer pulls and digitalisation as the antecedents of the disruptive technology have been assessed. Instead of their negative impact, the firms can utilise certain disruptive innovation to be beneficial for their competitive advantages if they know a way to deal with it.